Efektivitas Ekstrak Biji Mangga Harumanis terhadap Staphylococcus aureus, Bacillus subtilis, Shigella sp., dan Escherichia coli (EFFECTIVITY OF MANGO HARUMANIS SEED EXTRACT TO STAPHYLOCOCCUS AUREUS, BACILLUS SUBTILIS, SHIGELLA SP., AND ESCHERICHIA COLI) - Prihandani, Sri Suryatmiati; Noor, Susan Maphilindawati; ., Andriani; Poeloengan, Masniari (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
Mango (Mangifera indica L.) is a tropical fruit trees in the flowering plant. Mango has been reportedas an antibacterial. The experiment was conducted to analysis the secondary compounds in seed Mangiferaindica L. extract and to test the antibacterial of seed Mangifera indica L. Staphylococcus aureus, Bacillussubtilis, Shigella sp and Escherichia coli. The plants material was extracted by percolation with ethanol.The assays were performed by using paper diffusion for determination of inhibition zone and dilutionmethod for determination of minimum inhibitory concentration. The result showed that secondarycompounds in seed mango extract were flavonoid, triterpenoid, saponin. Seed mango extract hasantibacterial activity on Staphylococcus aureus, Bacillus subtilis, Shigella sp and Escherichia coli.
Keywords: Mangifera indica L. Extract, Staphylococcus aureus, Bacillus subtilis, Shigella sp and Escherichia coli